Increasing lysine level improved methanol assimilation toward butyric acid production in Butyribacterium methylotrophicum - Jing Wang; Yang Liao; Jialun Qin; Chen Ma; Yuqi Jin; Xin Wang; Kequan Chen; Pingkai Ouyang (Biotechnology for Biofuels and Bioproducts, 2023)
Abstract Background Methanol, a promising non-food fermentation substrate, has gained increasing interest as an alternative feedstock to sugars for the bio-based production of value-added chemicals. Butyribacterium methylotrophicum, one of methylotrophic-acetogenic bacterium, is a promising host to assimilate methanol coupled with CO2 fixation for the production of organic acids, such as butyric acid. Although the methanol utilization pathway has been identified in B. methylotrophicum, little knowledge was currently known about its regulatory targets, limiting the rational engineering to improve methanol utilization. Results In this study, we found that methanol assimilation of B. methylotrophicum could be significantly improved when using corn steep liquor (CSL) as the co-substrate. The further investigation revealed that high level of lysine was responsible for enhanced methanol utilization. Through the transcriptome analysis, we proposed a potential mechanism by which lysine confers improved methylotrophy via modulating NikABCDE and FhuBCD transporters, both of which are involved in the uptake of cofactors essential for enzymes of methanol assimilation. The improved methylotrophy was also confirmed by overexpressing NikABCDE or FhuBCD operon. Finally, the de novo synthetic pathway of lysine was further engineered and the methanol utilization and butyric acid production of B. methylotrophicum were improved by 63.2% and 79.7%, respectively. After an optimization of cultivation medium, 3.69 g/L of butyric acid was finally achieved from methanol with a yield of 76.3%, the highest level reported to date. Conclusion This study revealed a novel mechanism to regulate methanol assimilation by lysine in B. methylotrophicum and engineered it to improve methanol bioconversion to butyric acid, culminating in the synthesis of the highest butyric acid titer reported so far in B. methylotrophicum. What’s more, our work represents a further advancement in the engineering of methylotrophic-acetogenic bacterium to improve C1-compound utilization. Graphical Abstract